ello!!❤❤
In an equilateral triangle with side a, prove that
![1) \: altitude \: = \frac{a \sqrt{3} }{2} 1) \: altitude \: = \frac{a \sqrt{3} }{2}](https://tex.z-dn.net/?f=1%29+%5C%3A+altitude+%5C%3A++%3D++%5Cfrac%7Ba+%5Csqrt%7B3%7D+%7D%7B2%7D+)
![2) \: area \: = \frac{ \sqrt{3} }{4} {a}^{2} 2) \: area \: = \frac{ \sqrt{3} }{4} {a}^{2}](https://tex.z-dn.net/?f=2%29+%5C%3A+area+%5C%3A++%3D++%5Cfrac%7B+%5Csqrt%7B3%7D+%7D%7B4%7D+%7Ba%7D%5E%7B2%7D++)
Answers
An equilateral triangle is symmetrical so if you draw a perpendicular from point A to BC it bisects the side BC.
so CD=a/2
AD is the altitude(height) of the triangle ABC
In triangle ADC by pythagoras theorem :
AD^2 = a^2 - a^2/4 = 3a^2/4
AD =a√3/2
We know that area of a triangle = 1/2 base×height
so area of this triangle =
1/2 x (a√3/2) x a
= √3 a^2 / 4
![](https://hi-static.z-dn.net/files/d0e/d4503494fcdf9e8cf8e25dfba02a46bb.jpg)
Heya !!
Here is your solution :
Consider a equilateral ∆ABC in that AD is altitude on line BC.
Hence, in ∆ABC we shall get two other triangles named ∆ABD and ∆ACD.
Considering ∆ABD,
⇒AB = a ( Given ) [ Hypotenuse ( Side opposite to 90° ) ]
⇒BD = ( a/2 ) [ Altitude of an equilateral ∆ bisects its base ]
⇒<ADB = 90°
⇒AD = ?
Using Pythagoras Theorem,
⇒Hypotenuse² = Base² + Altitude²
⇒ a² = ( a/2 )² + AD²
⇒a² = ( a²/4 ) + AD²
⇒a² - ( a²/4 ) = AD²
⇒( 4a² - a² ) /4 = AD²
⇒ 3a²/4 = AD²
⇒ AD = √( 3a²/4 )
•°• AD = ( a√3 / 2 )
Proved !!
Now , For ∆ABC , we have,
⇒AC = Base = a
⇒AD = Corresponding Altitude = ( a√3 / 2 )
We know that,
⇒Area of an equilateral ∆ = ( 1/2 ) × Base × Corresponding Altitude
⇒Ar. of an equilateral ∆ = ( 1/2 ) × a × ( a√3/2 )
•°• Ar. of an equilateral ∆ = ( √3/4 )a²
Proved !!
![](https://hi-static.z-dn.net/files/df1/aa6f2cbb6ff0e129eab9924166e7f410.jpg)